HISTOPLASMOSIS - CASE REPORT - Aziz, Rizwan; Khan, Nisar; Qayum, Iftikhar; Khan, Abdur Rab (Journal of Ayub Medical College Abbottabad, 2002)
Histoplasmosis is one the chronic pulmonary diseases which can present just like pulmonary tuberculosis1,2. Acute pulmonary histoplasmosis is usually asymptomatic. Cough, fever and malaise with chest radiological findings of hilar adenopathy are typical features. Sometimes erythema nodosum or erythema multiforme may occur. Perinodal fibrosis may occur in rare circumstances if hilar nodes go through caseation and granuloma formation. In this manner progressive mediastinal fibrosis may occur. Clinical manifestations are of three types 3. The most common presentation in the vast majority of the patients is of acute pulmonary histoplasmosis, which is a mild infection. The other two manifestations are that of chronic pulmonary histoplamosis and the acute disseminated infection - these are progressively fatal and serious in outcome. The acute disseminated form occurs usually in immunocompromised, especially in AIDS. A wide spread of features may be found - fever, lymphadenopathy, hepatomegaly, splenomegaly, jaundice, leukopenia, chronic meningitis, endocarditis, granulomatous hepatitis, Addison’s disease and GIT ulceration. Some of the features overlap with chronic pulmonary histoplasmosis, which is usually localized as the main differentiating point. Chronic pulmonary histoplasmosis mimics tuberculosis of the lungs 1-3. Night sweats, weight loss and productive cough with chest radiology showing uni- or bilateral hilar adenopathy with fibronodular shadows in the upper zones of the lungs are the hallmark features. 33 percent of the cases improve spontaneously but the rest undergo cavitation of upper lobes or emphysematous bulla formation develops. The resultant cor pulmonale and recurrent bacterial infections kill the patient eventually. Histoplasma capsulatum is a dimorphic fungus that causes infection when a person inhales it 1, 3. It prefers to grow on moist surfaces and in soils especially having droppings of birds and bats. Infectivity can occur within 5-18 days after exposure to dust contaminated with its hyphae during raking, bulldozing, cave exploring and by cleaning the soiled floor of chicken droppings. The pathogenesis involves the inhalation of the small spores of this fungus into the alveoli and proliferation by budding. With the passage of time there is a granulomatous reaction leading to caseation necrosis and calcification that can produce a mass of scar tissue known as histoplasmoma 3. The pathology resembles the chronic process of granuloma formation in tuberculosis. Treatment of the disease includes intravenous amphotericin B (0.6 mg/kg daily) for the initial phase for acute dissemination in patients who are severely ill. The patient can be switched over to Itraconazole (200 mg twice daily) once improvement is evident 3, 4. Similarly chemotherapy can be given for chronic pulmonary fibronodular histoplasmosis but no treatment is required for acute pulmonary histoplasmosis.